(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the recent scenario, the solar energy play a vital role for domestic usages since it is being one of the renewable forms of energy. The spiral solar thermal collector is used to harvest the solar energy. In the present work, the spiral solar thermal collector with specified dimensions was fabricated and the readings were taken. A Rule Based Mamdani Type Fuzzy (RBMTF) model was developed to predict the output temperature of the spiral solar thermal collector, using the mass flow rate of water, time as input parameters and outlet temperature as an output parameter with an aid of MATLAB fuzzy logic toolbox. The rate of flow is varied between 0.014 and 0.0755 for the time range of 600 minutes to 960 minutes. Six phonological variables were considered for each combination and the R2 value for the testing data were about 96.9%. The predicted results were found to be in concurrence with the experimental results which confirm reliability of the proposed RBMTF model.